PENGARUH SELF ASSESSMENT SYSTEM, MONEY ETHICS, DAN TEKNOLOGI DAN INFORMASI PERPAJAKAN TERHADAP PERSEPSI WAJIB PAJAK BADAN MENGENAI TAX EVASION (STUDI KASUS PADA KPP PRATAMA LANGSA) - Razif Razif; Alqonitur Rasyidah (Al Mashaadir : Jurnal Ilmu Syariah, 2020)
This study aims to determine and analyze the influence of self-assessment system, money ethics, and technology and tax information on corporate taxpayer perception of tax evasion in KPP Pratama Langsa. The data used in this study is the primary data. The sample of this study is taken using purposive sampling. The sample in this research is 45 taxpayer of the construction agency registered in KPP Pratama Langsa. Data analysis method used is multiple linear regression analysis and processed using statistical program SPSS 22.0. The results showed that the self-assessment system has a negative and significant effect on corporate taxpayer perception of tax evasion, money ethics and technology and taxation information have a positive and significant effect on the corporate taxpayer perception of tax evasion in KPP Pratama Langsa.